LA CUSTODIA PROCESIONAL DEL PUENTE GENIL . REFLEXIONES SOBRE UNA OBRA DE PLATERÍA DEL SIGLO XVI - Rivas Carmona, Jesús (Imafronte, 1997)
Within the rich repertoy of processionol monstronces of Spain in the 16th century and in particirlar within the nutrid series that were created in Andalucia the monstronce of Puente Genil, in the province of Cordoba. must be included althougt was an item almost exclusively of local character. It was a work of art destined for o small population, such as old Puente Genil in the 16<sip>th century and did not have the category of the great monstrances of the period, but despite this fact shows the tremendous effort in the realisation of these structures, for the Corpus Christi procession even in these the greatness of the nobles to whow they belonged, in this specific case the Marquess of Priego and Lord of Aguilar. For this reason it is not surprising that a fine silversmith was used, apparently Diego Fernández, one of the most important master in this art in the Cordoba of that period.